The Economic Crisis of 2008 and World Shipping: Unheeded Warnings - Hercules E. Haralambides; Helen Thanopoulou (SPOUDAI - Journal of Economics and Business, 2014)
Cyclicality in shipping is inherent. However, the speed and amplitude of market changes, since the fateful collapse of Lehman brothers in 2008 - distinguishes this particular crisis from most previous cycles. Predictions and investment moves made until immediately before the crisis have, in retrospect, been proven erroneous. The same applies to many of freight rate forecasts made subsequently. Yet, the information for deciphering market signals was already there in the critical months before the crisis, the authors argue. The paper demonstrates that if investors had relied on certain very simple indices of over-investment in new ships, they would have concluded that the advent of an inflexion point was unavoidable. A market turn should have been anticipated even if favourable demand developments were to continue undisrupted. Indices such as the ratio of orderbook to the existing fleet had deviated manifold from their long-term average since the previous major cycle. The authors conclude that the nature of this last cycle, akin in many respects with the origins and course of the crisis of the 1970s and the 1980s was determined more by what Metaxas called in 1971 "endemic tendency to over-invest".
Keywords: E32; F17; E37; 330; shipping cycles; international trade; freight market forecasts